Prevention by the CXCR2 antagonist SCH527123 of the calcification of porcine heart valve cusps implanted subcutaneously in rats - Chabry, Yuthiline; Dhayni, Kawthar; Kamel, Saïd; Caus, Thierry; Bennis, Youssef (Frontiers in Cardiovascular Medicine, 2023)
Introduction Calcification is a main cause of bioprosthetic heart valves failure. It may be promoted by the inflammation developed in the glutaraldehyde (GA)-fixed cusps of the bioprosthesis. We tested the hypothesis that antagonizing the C-X-C chemokines receptor 2 (CXCR2) may prevent the calcification of GA-fixed porcine aortic valves. Materiel and methods Four-week-old Sprague Dawley males were transplanted with 2 aortic valve cusps isolated from independent pigs and implanted into the dorsal wall. Four groups of 6 rats were compared: rats transplanted with GA-free or GA-fixed cusps and rats transplanted with GA-fixed cusps and treated with 1 mg/kg/day SCH5217123 (a CXCR2 antagonist) intraperitoneally (IP) or subcutaneously (SC) around the xenograft, for 14 days. Then, rats underwent blood count before xenografts have been explanted for histology and biochemistry analyses. Results A strong calcification of the xenografts was induced by GA pre-incubation. However, we observed a significant decrease in this effect in rats treated with SCH527123 IP or SC. Implantation of GA-fixed cusps was associated with a significant increase in the white blood cell count, an effect that was significantly prevented by SCH527123. In addition, the expression of the CD3, CD68 and CXCR2 markers was reduced in the GA-fixed cusps explanted from rats treated with SCH527123 as compared to those explanted from non-treated rats. Conclusion The calcification of GA-fixed porcine aortic valve cusps implanted subcutaneously in rats was significantly prevented by antagonizing CXCR2 with SCH527123. This effect may partly result from an inhibition of the GA-induced infiltration of T-cells and macrophages into the xenograft.